Circadian Activity Rhythms for Mothers with an Infant in ICU - Lee, Shih-Yu (Frontiers Research Foundation, 2010)
Circadian rhythms influence sleep and wakefulness. Circadian activity rhythms (CAR) are altered in individuals with dementia or seasonal affective disorder. To date, studies exploring CAR and sleep in postpartum women are rare. The purpose of this report is to describe relationships between CAR, sleep disturbance, and fatigue among 72 first-time mothers during their second week postpartum while their newborn remain hospitalized in intensive care unit. Seventy-two mothers were included in this secondary data analysis sample from three separate studies. Participants completed the general sleep disturbance scale (GSDS), numerical rating scale for fatigue, and a sleep diary. The objective sleep data included total sleep time (TST), wake after sleep onset (WASO), and CAR determined by the circadian quotient (amplitude/mesor) averaged from at least 48-h of wrist actigraphy monitoring. The TST of mothers who self-reported as poor sleepers was 354 min (SEM = 21.9), with a mean WASO of 19.5% (SEM = 2.8). The overall sleep quality measured by the GSDS was clinically, significantly disrupted (M = 5.5, SD = 1.2). The mean score for morning fatigue was 5.8 (SD = 2.0), indicating moderate fatigue severity. The CAR was 0.62 (SEM = 0.04), indicating poor synchronization. The self-reported good sleepers (GSDS < 3) had better CAR (M = 0.71, SEM = 0.02) than poor sleepers (GSDS > 3) (t[70] = 2.0, p < 0.05). A higher circadian equation was associated with higher TST (r = 0.83, p < 0.001), less WASO (r = −0.50, p < 0.001), lower self-reported sleep disturbance scores (r = −0.35, p = 0.01), and less morning fatigue (r = −0.26). Findings indicate that mothers with a hospitalized infant have both nocturnal sleep problems and disturbed circadian activity rhythms. Factors responsible for these sleep and rhythm disturbances, the adverse effects on mother's physical and mental well-being, and mother–infant relationship require further study.